A thirsty little lizard: drinking by the pygmy bluetongue lizard. Issue 1 (2nd January 2016) - Nielsen, Torben P.; Ebrahimi, Mehregan; Bull, C. Michael
ABSTRACT: The pygmy bluetongue lizard ( Tiliqua adelaidensis ) is an endangered scincid lizard, endemic to the Mid North region of South Australia, where it occupies heavily fragmented patches of native grassland. Pygmy bluetongue lizards live in spider burrows and rarely venture far from their burrows. This limits their access to free standing water, and it was previously unknown whether lizards acquired all the water they needed from their food, or whether they could access an alternative source of water. This paper presents 27 observations of lizards drinking either from drops of morning dew or from rain drops accumulated on vegetation close to their burrow entrances. These observations suggest that pygmy bluetongue lizards can supplement their water requirements independent of free standing water sources, like streams or ponds, if there is vegetation that can collect dew and rain close to burrow entrances. Vegetation that can hold water droplets for a short time provides flexibility for the lizards in maintaining their water budgets. The water collecting function of vegetation should be included as a factor in short-term management decisions about the level of grazing in the lizard's habitat. In the longer term, the benefits of having plants that can accumulate water drops will need to be considered if suitable relocation sites are to be found.